Exome sequencing in 90 children with developmental delay: a single-center experience - Boyarchuk, Oksana; Volianska, Liubov; Smashna, Olena; Makukh, Halyna (Frontiers in Genetics, 2024)
IntroductionDevelopmental delay (DD) in children is often caused by genetic abnormalities, which are challenging to diagnose due to the vast genetic variability.MethodsThis study presents a detailed analysis of whole-exome sequencing (WES) on 90 children with DD at a single clinical center.ResultsWe identified pathogenic or likely pathogenic variants in 27.8% of cases, with 7.8% revealing variants of uncertain significance (VUS). Among the positive findings, 21 (84.0%) corresponded to the main clinical manifestations in patients, and 4 (16.0%) secondary findings provided new insights into the patient’s conditions. Positive and inconclusive cases led to a revision of the diagnosis or management plan in 34.4% of cases. The positive genetic result in children with Developmental delay was higher in the presence of epilepsy or seizures (odds ratio – 5.4444; 95% CI 2.0176 to 14.6918; p = 0.0008) and more than 3 dysmorphic features (odds ratio – 7.1739; 95% CI 1.7791 to 28.9282; p = 0.0056). Variants compatible with the clinical manifestations were identified in 11.9% of children with autistic spectrum disorders.ConclusionOur findings emphasize the utility of WES in clinical diagnostics, offering significant insights into patient management and potentially guiding therapeutic decisions.